Ocean warming enhances the competitive advantage of Ulva prolifera over a golden tide alga, Sargassum horneri under eutrophication - Wu, Hailong; Zhang, Jiankai; Li, He; Li, Sufang; Pan, Chen; Yi, Lefei; Xu, Juntian; He, Peimin (Frontiers in Marine Science, 2024)
Recent years have seen the Ulva green tide and Sargassum golden tide become commonplace in the coastal waters of China. However, little is known on how the combination of ocean warming and eutrophication would affect the interaction of green and golden tides. In this study, we cultured the green tide alga Ulva prolifera and the golden tide alga Sargassum horneri under different temperatures (5, 10, 15, 20, 25, and 30°C) and two nutrient concentrations (Low nutrient, LN: 5 μM-nitrate and 0.5 μM-phosphate; High nutrient, HN: 500 μM-N and 50 μM-P) in both monoculture and coculture systems to investigate the physiological responses and their competitive relationships. In monocultures, the growth of U. prolifera and S. horneri, along with pigment concentrations and photosynthesis, increased with rising temperature, reaching a plateau at 15 - 25°C. However, when the temperature increased to 30°C, the growth of U. prolifera and S. horneri decreased abruptly, with S. horneri even suffering death. In coculture, the growth of both U. prolifera and S. horneri was inhibited compared to the monoculture, with the greatest decline observed in S. horneri at 25°C under two nutrient conditions. Our results show that U. prolifera would outcompete S. horneri under high temperature in coculture, suggesting that ocean warming would enhance the competitive advantage of green tide over golden tide under eutrophication in the future.